PENGARUH KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TERHADAP PENGHINDARAN PAJAK(TAX AVOIDANCE) - Umi Wahidah; Sri Ayem (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This research aimed to examine the effect of the convergence of International Financial Reporting Standards (IFRS) on tax avoidance on companies listed in Indonesia Stock Exchange. Tax avoidance that used in this research was Cash Efective Tax Rate (CETR). This research is also use the control variable to get other different influence that different such as CSR, size, and earning management (EM. This research used populations sector of transport service companies that listed in Indonesia Stock Exchange. The data of this research taken from secondary data that was from the Indonesia Stock Exchange in the form of Indonesian Capital Market Directory (ICMD) and the annual report of the company 2011-2015. The method of collecting sample was purposive sampling technique, the population that to be sampling in this research was populations that has the criteria of a particular sample. Companies that has the criteria of the research sample as many as 78 companies. The method of analysis used in this research is multiple regression analysis. Based on regression testing shows that the convergence of International Financial Reporting Standards (IFRS) has a positive and significant impact on tax evasion. This shows that IFRS convergence actually improves tax evasion practices. The control variables of firm size and earnings management also significantly influence the application of IFRS in improving tax avoidance practices, while CSR control variables have no role in convergence IFRS in improving tax evasion practice.